A Global Survey of Lithospheric Flexure at Steep‐Sided Domical Volcanoes on Venus Reveals Intermediate Elastic Thicknesses. Issue 7 (22nd July 2021) - Borrelli, M. E.; O'Rourke, J. G.; Smrekar, S. E.; Ostberg, C. M.
Abstract: Topographic flexure in response to vertical loads reveals key lithospheric properties, including elastic thickness and the heat flow from the interior. Flexural stresses that depend on elastic thickness may in turn control volcano morphology. One previous study predicted that steep‐sided domes on Venus usually form where the elastic thickness is ∼15–40 km. Coronae and large volcanoes may typically form at regions with lower and higher elastic thickness, respectively. We surveyed flexural signatures around steep‐sided domes and confirmed this hypothesis. Specifically, we extracted radial profiles of topography from Magellan altimetry data and a new elevation model derived from stereo images. Nearly 20% of the identifiable domes had topographic profiles that were amenable to flexural interpretations. We determined elastic thicknesses using a curve‐fitting algorithm and plate bending models that treat each volcano as either a Cartesian line load or an axisymmetric disc load. We used a yield strength envelope featuring brittle failure and ductile flow at the top and bottom of the lithosphere, respectively, to convert elastic thickness into mechanical thickness and surface heat flow. The average elastic thickness for domes not near coronae is ∼30 km, corresponding to a heat flow of ∼60 mW/m 2 . Coronae on Venus are typically associated with elastic thicknesses of <10–15 km. Domes near coronae yielded elastic thicknesses in that range, and higher heat flows than domes not near coronae. Ultimately, flexural signatures are probably abundant around volcanic and tectonic features and would be further revealed in higher‐resolution topographic data. Plain Language Summary: Volcano shape as seen on the surface can be used to learn about the interior of a planet. Others have hypothesized that steep‐sided dome volcanoes (also called pancake domes) on Venus likely form where the lithosphere is ∼10–40 km thick, while many oval‐shaped features called coronae, which are enigmatic volcanic‐tectonic constructs, are likely to form where the lithosphere is ∼10 km or thinner. These features act as a load on the surface, causing the underlying plate to bend. We located the domes that show evidence of this flexural bending and matched topographic data to an analytic model with a curve‐fitting algorithm to determine the thickness of the idealized elastic plate. We then used a model of rock mechanics to infer the thickness of the real plate and thus the temperature gradient within the plate and the heat flow to the surface. Our results for elastic thickness at steep‐sided domes matched prior predictions, supporting the hypothesis that plate bending influences the shapes and sizes of volcanic features on Venus. If we sent a new mission to Venus to collect better data, then we could perform this type of analysis more precisely for a plethora of volcanic and tectonic structures. Key Points: We conducted the first global survey of lithospheric flexure at steep‐sided domical volcanoes (pancake domes) on Venus Steep‐sided domes on Venus are typically but not always located in regions with inferred elastic thicknesses between ∼15 and 40 km Domes near coronae are associated with lower elastic thicknesses and higher surface heat flows, consistent with prior studies of coronae